EPISTIMOLOGI AS-SUNNAH DALAM KAJIAN FILSAFAT HUKUM ISLAM - Muhazir Muhazir (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2018)
The Sunnah experienced a very rapid development in the course of the study of the Sunnah, many studies of the Sunnah which discussed it with various approaches, say golzhiher analyzing the As-Sunnah from the context of the sanad with a historical approach, studies of the Sunnah were studied by many people orentalis in various disciplines of science, they try to put forward new theories in order to examine and criticize the Sunnah of the Prophet which was caused by experiencing the purity of the text because there was interference after the Prophet died. Many criticisms occur and result in Muslim scholars who after completing and completing their education try to study with hermeneutical approaches.